Oil Palm Based Cellulose Esters as Raw Material for Environmentally Friendly Bio-plastic - Tjahjono Herawan; Meta Rivani; Halimatudahliana Halimatudahliana; Suryo Irawan (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2018)
Besides producing oil, oil palm is also produces huge amount of biomass such as empty fruit bunch. Both of those products had a potential to be used as a source of plastic raw materials called bio-plastics. Long-chain fatty acid source can be obtained from crude palm oil (palmitic acid and oleic acid) and palm kernel oil (lauric acid) while cellulose can be obtained from oil palm empty fruit bunch waste (OPEFB). Cellulose was produced from OPEFB by alkaline process on pilot plant scale. The yield of α-cellulose obtained as much as 32-38% of the OPEFB processed. The cellulose ester was synthesized by esterification reaction between cellulose of OPEFB and modified fatty acid from palm oil in a mild condition. Conversion of cellulose ester produced reached 92.7% with percent increase weight reach 460%, Degree Substitution (DS) 2.21 and melting point 201 oC. The tensile strength of the cellulose ester film was lower than tensile strength of petroleum-based plastics (Low Density Poly Ethylene/LDPE), which averaged 73 kg/cm2 versus 108 kg/cm2, so it was necessary to add additives to increase tensile strength and elasticity properties.